2020
DOI: 10.1002/adsc.202000354
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Catalytic Asymmetric Synthesis of Atropisomeric Hexatomic N‐Heterobiaryls

Abstract: Axially chiral hexatomic N‐heterobiaryls are among the most important class of structures with extensive utility in asymmetric catalysis as chiral ligands and organocatalysts, as exemplified by QUINAP and QUINOX. Besides, these atropisomers have attracted broad attention due to their application in drug discovery. Hence, it is not surprising that extensive efforts have been devoted for the pursue of efficient catalytic asymmetric methods for their direct and atroposelective construction. In addition to the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Readers shall refer to outstanding specialized reviews, which are codified according to catalysts (organocatalysts, peptidic catalysts and transition metal catalysts), synthetic strategies (direct C–H arylation, arene formation, desymmetrization, chirality conversion , and kinetic resolution) as well as compound classes (biaryls, , heterobiaryls, , nonbiaryls, multiple-axes system and natural products , ) for prior works and more specialized perspectives. A monograph covering synthesis, applications and bioactivities of atropisomers edited by José M Lassaletta has also been printed recently…”
Section: Introductionmentioning
confidence: 99%
“…Readers shall refer to outstanding specialized reviews, which are codified according to catalysts (organocatalysts, peptidic catalysts and transition metal catalysts), synthetic strategies (direct C–H arylation, arene formation, desymmetrization, chirality conversion , and kinetic resolution) as well as compound classes (biaryls, , heterobiaryls, , nonbiaryls, multiple-axes system and natural products , ) for prior works and more specialized perspectives. A monograph covering synthesis, applications and bioactivities of atropisomers edited by José M Lassaletta has also been printed recently…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of atropisomeric compounds by Christie and Kenner in 1922, the synthesis and application of these compounds in catalysis, natural products, and pharmaceutics have been extensively studied with significant advances reported during the last decades. However, highly atroposelective C–C bond formations, especially in the context of complex and highly substituted nitrogen-rich heterocycles, remain elusive to date (Scheme A). Among the very limited number of reported examples, most involved atroposelective formation of a heterocycle containing noncoordinating nitrogen such as indole or carbazole. Similarly, atroposelective C–C bond formations via Negishi coupling are rare in the literature. The few known examples focus on the synthesis of substituted biaryls, specifically binaphthalenes and biphenyls, with limited scope and moderate atroposelectivities (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…Several ligands, such as BINAPINE, Quinazox, and atropisomers, as shown in Figure , bearing both axial and point chirality have been reported in previous decades (Figure ). An alternative way to achieve the aforementioned objective is to combine the atropisomeric ligand with chiral additives. For example, in 1998, Mikami and Noyori found that a 1:1 molar ratio of ( R )-TolBINAP and ( S , S )-DPEN was far more efficient for the Ru-catalyzed hydrogenation of 2,4,4-trimethyl-2-cyclohexenone than the ( R )-diphosphine/( R , R )-diamine combination .…”
Section: Introductionmentioning
confidence: 99%